Plastics in food packaging properties, design, and fabrication - Brown, William E. (Packaging and converting technology, 1992)
Abundant, detailed information on how plastics are used in modern food distribution and the qualitative and quantitative linkages between food requirements and plastics' fabrication and performance. Covers technical properties, fabrication methods, economics, design calculations, regulations, use of